Pengaruh Pengungkapan Emisi Karbon, Eco-Efficiency dan Pertumbuhan Penjualan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Marini; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of carbon emissions disclosure, eco-efficiency and sales growth on company value with profitability as a mediating variable. The sample in this study used a purposive sampling method. Based on sample criteria, there were 24 samples used. The data analysis technique used uses panel data. The application used in this research uses Eviews 9. The research results prove that disclosure of carbon emissions and sales growth have no effect on company value, while eco-efficiency has a positive effect on company value. Simultaneously, disclosure of carbon emissions, eco-efficiency and sales growth influences company value.